Stanniocalcin-1 Regulates Re-Epithelialization in Human Keratinocytes - Yeung, Bonnie H. Y. (Public Library of Science, 2011)
Stanniocalcin-1 (STC1), a glycoprotein hormone, is believed to be involved in various biological processes such as inflammation, oxidative responses and cell migration. Riding on these emerging evidences, we hypothesized that STC1 may participate in the re-epithelialization during wound healing. Re-epithelialization is a critical step that involves keratinocyte lamellipodia (e-lam) formation, followed by cell migration. In this study, staurosporine (STS) treatment induced human keratinocyte (HaCaT) e-lam formation on fibronectin matrix and migration via the activation of focal adhesion kinase (FAK), the surge of intracellular calcium level [Ca(2+)]i and the inactivation of Akt. In accompanied with these migratory features, a time- and dose-dependent increase in STC1 expression was detected. STC1 gene expression was found not the downstream target of FAK-signaling as illustrated by FAK inhibition using PF573228. The reduction of [Ca(2+)]i by BAPTA/AM blocked the STS-mediated keratinocyte migration and STC1 gene expression. Alternatively the increase of [Ca(2+)]i by ionomycin exerted promotional effect on STS-induced STC1 gene expression. The inhibition of Akt by SH6 and GSK3β by lithium chloride (LiCl) could respectively induce and inhibit the STS-mediated e-lam formation, cell migration and STC1 gene expression. The STS-mediated e-lam formation and cell migration were notably hindered or induced respectively by STC1 knockdown or overexpression. This notion was further supported by the scratched wound assay. Collectively the findings provide the first evidence that STC1 promotes re-epithelialization in wound healing.